Growth, Reduction, and Survival of Bacteria on Tomatoes - Angela M. Valadez; Keith R. Schneider; Michelle D. Danyluk (EDIS, 2012)
Tomato producers are committed to taking proactive steps to ensure and enhance the safety of their fresh-market tomatoes, but even with better food safety controls, the risk for outbreaks of illness associated with tomato consumption still exists. This 32-page fact sheet highlights current tomato safety related studies on the growth, reduction, and survival of bacteria on fresh-market tomatoes. The authors evaluated bacterial studies on natural antimicrobials and detergents, as well as food processing, cross-contamination, and shelf-life studies. Written by Angela M. Valadez, Keith R. Schneider, and Michelle D. Danyluk, and published by the UF Department of Food Science and Human Nutrition, May 2012.